Is Bacterial Vaginosis Associated with an Increased Risk of Pelvic Organ Prolapse in Women? : A Comprehensive Systematic Review - Petra Damiana Anindita; Elvantie; Galih Dwi Endrianto; Namira (The Indonesian Journal of General Medicine, 2026)
Introduction: Bacterial vaginosis (BV) is the most common vaginal infection in reproductive-aged women, characterized by depletion of protective Lactobacillus species and overgrowth of anaerobic bacteria. Pelvic organ prolapse (POP) is a prevalent pelvic floor disorder with significant morbidity. Although both conditions share common risk factors such as aging, parity, and estrogen decline, whether BV independently increases POP risk remains unclear. This systematic review aims to synthesize available evidence on the association between BV and POP. Methods: A comprehensive systematic review was conducted using predefined screening criteria. Studies were included if they involved adult non-pregnant women, assessed BV as an exposure, measured POP as an outcome, provided clear diagnostic criteria for both conditions, and employed observational designs. Data extraction encompassed study characteristics, BV and POP assessment methods, effect measures, confounders, and temporal relationships. Results: Twenty-two sources were reviewed, including primary studies, systematic reviews, and narrative reviews. Only one primary study (Cheng et al., 2022) directly examined the BV-POP association in 358 postpartum women, finding significantly higher BV incidence in the pelvic floor dysfunction group (p<0.05), but BV was not an independent risk factor on logistic regression. Kaminskyi et al. (2020) observed vaginal biocenosis disorders in women with early genital prolapse but reported no statistical analysis. Indirect evidence from Yu et al. (2023) demonstrated associations between vaginal microenvironment factors (lactobacilli depletion, leukorrhea cleanliness) and pelvic dysfunction. Balaouras et al. (2024) identified Gardnerella among species associated with pelvic floor dysfunction. Alnaif et al. (2001) found smoking independently associated with both severe prolapse and BV, suggesting shared environmental risk factors. Wojtas et al. (2024) reported that up to 30% of pessary users develop BV, indicating possible reverse causation. Discussion: The current evidence does not support BV as an independent risk factor for POP. The observed co-occurrence is more plausibly explained by shared risk factors (age, menopause, estrogen decline, smoking) and reverse causation whereby anatomical changes of prolapse or pessary use promote dysbiosis. Broader vaginal microecological disturbances—particularly Lactobacillus depletion—may be more relevant than BV per se. Mechanistic pathways involving inflammation and collagen degradation remain speculative. Conclusion: Bacterial vaginosis is not established as an independent risk factor for pelvic organ prolapse. Well-designed prospective cohort studies with long-term follow-up, adequate confounder control, and standardized diagnostic criteria are needed to clarify this relationship.